The failure of the troika in Athens: Foreign assistance does not show Greece the way out of the crisis - Heribert Dieter; Annkathrin Frind (Stiftung Wissenschaft und Politik (SWP), 2012)
Even after the successful restructuring of Greek's sovereign debt in March 2012, most economic problems of the country remain unsolved. The non-competitive economy of the EU member country requires a comprehensive transformation. Many observers agree that a fundamental restructuring of the Greek economy is essential to ensure future prosperity. However, the troika - composed of the International Monetary Fund, the European Commission, and the European Central Bank - hitherto concentrated on telling Greek society what ought to be done. Despite sufficient evidence that such an approach has failed many times in development cooperation and in the transformation of economies in eastern Europe, the troika continues to implement its flawed approach. Greece does not need more foreign advisers but rather has to develop macro- and microeconomic concepts and strategies for the improvement of the competitiveness of enterprises. The country has to develop ownership of its reform process, instead of fighting recipes imposed by the troika. There are many examples of successful economic development in recent economic history, but foreign help and recipes never played the decisive role
Keywords: 320